The compromises and flexibility of TEI customisation - Cummings, J (Humanities Research Institute, University of Sheffield, 2014)
The ongoing efforts of the Text Encoding Initiative (TEI) have produced a wide-ranging set of Guidelines for encoding textual phenomena. However, standardisation attempts such as this always make compromises in order to achieve their goals. The recommendations of the TEI are no exception to this and this paper examines at some of these compromises along with the benefits and drawbacks they bring. The TEI's extremely flexible method for documenting customisations and extensions will be also considered and how it might benefit interoperability amongst sub-communities of users.